The Stone and its Images: The Poetry of Nancy Morejón - Alan West (Studies in 20th & 21st Century Literature, 1996)
The essay explores the roots of Nancy Morejón's poetry within the context of a transculturated afro-Cuban identity. Beginning by an examination of the poems that directly deal with the orishas of santería, the essay moves on to some of her more lyric poetry. Morejón's relationship to Dulce María Loynaz provides particular interest in how both writers treat the metaphor of the house in two important poems. This is followed by a discussion of some of Morejón's overtly feminist poetry, placed both within a Cuban context of the history of its revolution, and the displacement of exile (in dialogue with Cuban women outside the island). Morejón's aesthetic scope is wide and her affinities with Poe, the French symbolists, the Cuban poetic tradition, and the plastic arts (Mendive, Brueghel), as well as the essays of Bachelard, are drawn upon to understand the multiple sources of her work. Throughout the essay different critical methods are brought to bear on how Morejón weaves together nature, politics, myth, aesthetic insight, and personal testimony in a poetry with enormous historical resonance.
Keywords: Afra-hispanic writers; women writers; Nancy Morejón; afro-Cuban identity; identity; Cuban literature; poetry; lyric poetry; Dulce María Loynaz; feminist poetry; feminism; exile; homeland; Cuban women; plastic arts; nature; politics; myth; aesthetics; history